Benign Adult-Type Osteopetrosis with Recurrent Osteomyelitis of the Maxilla—A Rare Case Report - Nalini Aswath; R. Bhargavi (Indian Journal of Dental Research)
Osteopetrosis, also known as marble bone disease, is a genetic condition characterised by generalised sclerosis of bones. The osteoclastic cells responsible for bone resorption are defective and nonfunctional. These patients tend to have low bone quality in spite of increased bone deposition and thus experience multiple fractures during their life span. The bones are dense with loss of corticomedullary differentiation. A case report of benign adult type of osteopetrosis wherein a 47-year-old man underwent simple dental extraction of maxillary posterior teeth that segued to chronic nonhealing osteomyelitis of the maxilla is presented. Sequestromy of the dead bone further complicated the secondary infection due to nonhealing of the surgical area. The patient was treated with a full course of antibiotics and is under regular follow-up. Since dental extractions can lead to osteomyelitis of jaw bones judicious evaluation and careful treatment planning are advised.